O pojmu "boha" v Platónově myšlení = On notion of "God" in Plato's thinking - Boštík, Martin (Religio, 2003)
Because of Plato did not use a steady terminology there are several various meanings of a notion of "god" in his dialogues depending on concrete contexts. Adjective divine sometimes means nothing connected with deity but only "great, outstanding or wonderful". Plato used this adjective in a comparative and superlative degree, often in an ironical way. It can be often found in connection with anything what is regarded to be supernatural like a poetic inspiration or a prediction ability. Plato took over some meanings of a notion of "god" from his contemporary religious tradition and modified them according to his philosophy; the others are results of his own original thinking. (1) Soul is a divine substance. It is simple (according to Phaedo 80b) and rational which means that is the most similar to ideas. The most valuable part of souls is reason, which comes directly from Demiurgos (Timaeus 41c). Soul is a source of spontaneous movements of all material substances too (Laws 899a). Connection of reason and soul (which is a feature of personality) is the main feature of Plato's god. (2) Cosmos is divine. It is a living being under control of fully rational Soul of Cosmos, which contains all living creatures (Timaeus 30b). It is a real god. (3) All stars and planets are gods because of their rational souls. They are the most perfect kinds of all living beings with the most beautiful bodies and the best souls (Epinomis 981e). (4) Creator - Demiurgos is called a god (Timaeus 31c). Demiurgos created Cosmos according to patterns of eternal ideas and so he can be understood as a personification of reason. (5) God discussed in Republic (382d) is described like simple, changeless and absolutely truthful. Popper calls these attempts of purifying "changing into immobile beings in Parmenides style". (6) There is another conception of deity in Laws which could be called a conception of "full-blooded god". Such gods are worshiped by cults coming from Delphi. People can ask them for grace and help and can judge and condemn in their names. These gods take care for people (712b-716d). In Wyller's opinion this conception of god represents "Greek Jehovah" and in Gilson's opinion it is a real expression of Plato's own religiosity. (7) Plato also talks about "eternal (immortal) gods" in Timaeus (37c). They are patterns for Cosmos created by Demiurgos. It means that an expression "eternal (immortal) gods" is a metaphor for ideas. (8) If we analyse Plato's ontology it is necessary to recognize a higher status of "idea of Goodness" among the other ideas. That is the reason why a lot of thinkers mean that this idea plays a role of God in his ontology (I would say a role of the highest god in systems of inclusive monotheism).